Kant, Shelley and the Visionary Critique of Metaphysics - Bassler, O. Bradley (Springer International Publishing, 2018)
This book addresses the philosophy of Kant and the poetry of Shelley as historical starting points for a new way of thinking in the modern age. Fusing together critical philosophy and visionary poetry, Bassler develops the notion of visionary critique, or paraphysics, as a model for future philosophical endeavor. This philosophical practice is rooted in the concept of the indefinite power associated with the sublime in both Kant and Shelley's work, to which the notion of the parafinite or indefinitely large is extended in this book.